Would the Real Pioneers Please Stand up? : Confronting the Ambiguous Narrative of the Dutch Sonderweg in the Late Middle Ages - Geens, Sam (TSEG - The Low Countries Journal of Social and Economic History, 2024)
In Pioneers of Capitalism, Maarten Prak and Jan Luiten van Zanden construct a masterful narrative of the Dutch economy in premodern times. Through the Dutch case, the authors show that capitalism can also have sustained positive effects whenever this mode of production is combined with a strong civil society. Institutions of cooperation, such as guilds or representative bodies, may serve as a check on the pursuit of unlimited profit. Two questions are central to the book: why was the Netherlands one of the pioneers of capitalism, and what was its impact on Dutch society? While the other contributions in this issue focus primarily on the latter question, I will concentrate my reflections on the former.